Bisphenol a induces steatosis in HepaRG cells using a model of perinatal exposure. Issue 3 (20th June 2016) - Bucher, Simon; Jalili, Pégah; Le Guillou, Dounia; Begriche, Karima; Rondel, Karine; Martinais, Sophie; Zalko, Daniel; Corlu, Anne; Robin, Marie‐Anne; Fromenty, Bernard
ABSTRACT: Human exposure to bisphenol A (BPA) could favor obesity and related metabolic disorders such as hepatic steatosis. Investigations in rodents have shown that these deleterious effects are observed not only when BPA is administered during the adult life but also with different protocols of perinatal exposure. Whether perinatal BPA exposure could pose a risk in human is currently unknown, and thus appropriate in vitro models could be important to tackle this major issue. Accordingly, we determined whether long‐term BPA treatment could induce steatosis in human HepaRG cells by using a protocol mimicking perinatal exposure. To this end, the kinetics of expression of seven proteins differentially expressed during liver development was determined during a 4‐week period of cell culture required for proliferation and differentiation. By analogy with data reported in rodents and humans, our results indicated that the period of cell culture around day 15 and day 18 after seeding could be considered as the "natal" period. Consequently, HepaRG cells were treated for 3 weeks with BPA (from 0.2 to 2000 nM), with a treatment starting during the proliferating period. BPA was able to induce steatosis with a nonmonotonic dose response profile, with significant effects on neutral lipids and triglycerides observed for the 2 nM concentration. However, the expression of many enzymes involved in lipid and carbohydrate homeostasis was unchanged in exposed HepaRG cells. The expression of other potential BPA targets and enzymes involved in BPA biotransformation was also determined, giving answers as well as new questions regarding the mechanisms of action of BPA. Hence, HepaRG cells provide a valuable model that can prove useful for the toxicological assessment of endocrine disruptors on hepatic metabolisms, in particular in the developing liver. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1024–1036, 2017.